Experimental investigation of a cooking unit integrated with thermal energy storage system - Pamella, K. Kajumba; Denis, Okello; Karidewa, Nyeinga; Ole, J. Nydal (Journal of Energy Storage, 2020)
The thermal performance of a newly developed cooking unit integrated with a thermal energy storage (TES) system suitable for solar thermal applications has been tested and analysed. The experimental set-up consisted of a TES tank, connecting pipes, a manual control valve and a cooking unit. Sun flower oil was used as both the heat storage material and heat transfer fluid. The heat transfer was such that hot oil flowed by gravity from the TES tank through a pipe to the bottom of the cooking unit, which was in contact with the oil. The flow of the oil was controlled by a manual valve fixed on the connecting pipe to the cooker unit. Cooking experiments were carried out by boiling known quantities of water and food items at different flow rate settings. The results showed that the heating rate increased with increasing flow rates, and the efficiencies of the cooking unit were obtained as 40%, 43% and 52% for flow rates settings of 4 ml/s, 6 ml/s and 12 ml/s respectively. The rate of heat loss in the cooking unit was determined, and the overall heat loss coefficient was found to be about 0.54 W/K. Energy balances were used to estimate the heat transfer coefficients between the hot oil and the water in the cooking pot at different flow rates. The results showed that a high flow rate setting of 12 ml/s gave the highest heat transfer rate while a very low flow rate setting of 4 ml/s reduced the heat transfer rate, but also retained heat for longer periods. The heat transfer rate was found to be on the average 120 W/m2K. The manual valve makes it possible to control the heating rate and adjust the flow rate to suit the needs of a particular food. With a well-insulated cooker, a very low flow rate can be used for foods that require longer cooking times.